Amyloid myopathy and myeloma: response to treatment. Issue 736 (February 1987) - Sheehan-Dare, R. A.; Simmons, A. V.
Abstract : A 57 year old female presented with an amyloid myopathy in association with lambda light chain myeloma. Treatment with melphalan and prednisolone resulted in remission of both myeloma and myopathy.